Analysis of the Implementation of the Government Internal Control System (SPIP) at the Regional Inspectorate of East Nusa Tenggara Province - Leu, Theresia Fouk; Wahyuningrum, Christiana (Jurnal Ilmiah Global Education, 2025)
Implementation of the Government Internal Control System (SPIP) at the Regional Inspectorate of East Nusa Tenggara Province is carried out. Based on the formulation of the problem, the objective of this research is to describe the implementation of the Government Internal Control System (SPIP) at the Regional Inspectorate of East Nusa Tenggara Province. The data analysis technique used is descriptive qualitative analysis, in which data obtained from respondents will subsequently be analyzed using the Miles and Huberman model. The results of the data analysis carried out using the Miles and Huberman model show that the results obtained from interviews with 10 respondents indicate that the indicators of SPIP elements, namely the Control Environment, Risk Assessment, Control Activities, Information and Communication, and Monitoring, have been implemented. However, the implementation has not yet been optimal because there are still limitations in the understanding and competence of employees regarding principles and mechanisms of SPIP, as well as the lack of commitment, coordination, and support from Regional Apparatus Organizations (OPD).